Newspaper cuttings collected by Florence O'Donoghue with typescript extracts from the 'Cork Examiner' - O'Donoghue, Florence, 1895-1967 (1917)
Cuttings relate to the history of the I.R.A. and its members, independence movements in Cork and Kerry and various commemorations.
Keywords: Irish Republican Army; Ireland -- History -- 1922-; Ireland -- History -- Autonomy and independence movements